Errores de medicación en pacientes ambulatorios de Colombia 2005-2013 - Moreno-Gutiérrez, Paula Andrea; Machado-Alba, Jorge Enrique; Moncada-Escobar, Juan Carlos (Revista Médica de Risaralda, 2015)
Errores